Forecasting pandemic quarantine in New Zealand and Australia: A scoping review of quarantine characteristics and capabilities within preparedness plans and pandemic exercise reports from 2002 to 2019 - Matiu Bush; Stéphane L. Bouchoucha; Ana Hutchinson; Catherine M. Bennett (Journal of Infection and Public Health, 2023)
Background: This scoping review aims to identify and critically review quarantine preparedness in New Zealand and Australia pre-COVID-19 by categorising, comparing, and evaluating quarantine information contained within pandemic plans and exercises from both countries. Methods: Parliamentary websites, including Archives New Zealand, ParlInfo and Google Scholar, were searched for publicly available plans and exercise reports from 2002 to 2019. Data were extracted from documents meeting the inclusion criteria and analysed using directive content analysis based on the Australian Disaster Preparedness Framework categories. This scoping review followed the Joanna Briggs Institute methodology for scoping reviews, which guided the data extraction, analysis, and presentation of results. Results: A total of 16 documents mentioned quarantine and were included in this scoping review. The emphasis and level of detail regarding quarantine characteristics and capabilities varied between New Zealand's five documents (one plan and four exercise reports) and Australia's 11 documents (one Influenza pandemic plan, eight state plans and two exercise reports). New Zealand’s plan forecasted the need for both voluntary quarantine at home and involuntary quarantine in facilities for incoming travellers, whilst the Australian Influenza pandemic plan and state plans primarily considered voluntary quarantine within private residences. Capability gaps identified during exercises were not consistently incorporated into revised plans. Some government documents containing information on quarantine may not be publicly available, limiting the available evidence for this review. Conclusion: This scoping review highlights the need to incorporate a range of possible quarantine options into plans and preparation activities to test and identify gaps in government and responsible agencies' capabilities. Pandemic preparedness will be strengthened by incorporating quarantine scale and duration variables into exercise scenarios.